Glycosyl‐Modified Diporphyrins for in Vitro and in Vivo Fluorescence Imaging. Issue 8 (3rd May 2013) - Wu, Ming; Yu, Zuo‐Wei; Liu, Yang; Feng, Dao‐Fu; Yang, Jia‐Jia; Yin, Xue‐Bo; Zhang, Tao; Chen, Dong‐Yan; Liu, Tian‐Jun; Feng, Xi‐Zeng
Abstract The application of probes for optical imaging is becoming popular as they have high safety and good biocompatibility. We prepared two kinds of glycosyl‐modified diporphyrins, and their potentials as fluorescent probes were tested for the first time. After preparation of the glycosyl‐modified porphyrin monomers, Ag‐promoted coupling of the monomers was used to obtain glucose‐modified porphyrin dimer (GPD) and lactose‐modified porphyrin dimer (LPD). The strong interaction between the two porphyrin rings achieves red‐shifted emission, and thus circumvents autofluorescence and light‐scattering in biological samples. Although the glycosylation improves solubility, it also yielded selective attachment to cell membranes, and to chorions of early developmental‐stage zebrafish. Patch‐clamp experiments revealed the biocompatibility and low toxicity of GPD and LPD. Moreover, an in vivo imaging experiment provided direct evidence that zebrafish chorion contains sugar‐binding proteins. The modification and derivatization make porphyrins potential bioimaging probes for specific optical imaging.